IMPLEMENTASI PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA DI DESA BATIN WEH PONGAS KECAMATAN BUKIT KABUPATEN BENER MERIAH - Zunafriesma, Nanda (Saraq Opat: Jurnal Administrasi Publik, 2025)
Poverty is a condition of economic inability to meet the average living standards of people in an area. Direct Cash Assistance (BLT) is assistance in the form of cash to underprivileged (poor) families in the Village which is sourced from Village funds to minimize poverty rates for poor people in meeting their daily needs. This research aims to determine the implementation of the Direct Cash Assistance Program for village funds in Batin Weh Pongas village, Bukit District, Bener Meriah Regency. This type of research is descriptive qualitative. Informants for this research include the Bener Meriah Regency Social Service, the Head of Batin Weh Pongas Village, families who receive direct cash assistance benefits, and related stakeholders. The research results show that the BLT program can be said to have not been effective as a whole. Thus, the BLT program has several problems, namely: 1. Accuracy in making choices, 2. Accuracy of targets, 3. Organizational Commitment. The recommendations formulated include the data collection process, consolidation and verification process, validation process and determination of periodic data collection results and involvement of stakeholders in preparing the BLT program so that it is maximally supervised. Keywords: Poverty, Direct Cash Assistance, Village Funds